1995
DOI: 10.1148/radiology.196.3.7644632
|View full text |Cite
|
Sign up to set email alerts
|

Artificial widening of the mediastinum to gain access for extrapleural biopsy: clinical results.

Abstract: Artificial widening of the extrapleural space provides an access route to the anterior and posterior mediastinum for large-bore biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Preoperative recognition of risk factors may lead to their correction, by administration of antitussives or bronchodilatators [54], or to the use of more sophisticated techniques, such as a co-axial needle technique, using a larger needle as a guide. In all cases, transgression of the needle through bullae should be avoided and the needle path through the normal lung should be kept to a minimum [80,81] (®g. 3).…”
Section: Complicationsmentioning
confidence: 99%
“…Preoperative recognition of risk factors may lead to their correction, by administration of antitussives or bronchodilatators [54], or to the use of more sophisticated techniques, such as a co-axial needle technique, using a larger needle as a guide. In all cases, transgression of the needle through bullae should be avoided and the needle path through the normal lung should be kept to a minimum [80,81] (®g. 3).…”
Section: Complicationsmentioning
confidence: 99%
“…This technique was previously used for pulmonary and mediastinal lesions [9,10], but the only author that described its use for adrenal lesions was Karampekios et al [11]. In our study, despite the reduced sample size, the method proved to be safe with no reported complications.…”
Section: Discussionmentioning
confidence: 53%
“…Multiple scans are obtained between incremental needle advancement to check trajectory to ensure internal mammary vessels are not in path. A 22 gauge needle can be used inject saline solution or dilute contrast medium to widen the mediastinum and create an artificial extra-pleural path for needle placement [1,4]. After creation of a safe extra-pleural window, a 22 gauge needle is removed and a large bore needle (18-gauge or larger) guide needle is advanced.…”
Section: Discussionmentioning
confidence: 99%
“…After creation of a safe extra-pleural window, a 22 gauge needle is removed and a large bore needle (18-gauge or larger) guide needle is advanced. By using a coaxial technique, fine-needle aspiration and core biopsies are performed through the guide needle [1,4].…”
Section: Discussionmentioning
confidence: 99%